1970
DOI: 10.4314/sajas.v45i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Visual evaluation of beef tenderness by using surface structural observations and its relationship to meat colour

Abstract: The study describes the relationship between visual and instrumental measurements for colour and tenderness between five South African beef breeds: Bos indicus (Brahman), Sanga type (Nguni), British Bos taurus (Angus), European Bos taurus (Charolais) and the composite (Bonsmara). Ten animals per genotype were used (total = 50). The carcasses were split and the right sides were electrically stimulated, while the left sides were not stimulated. Steaks were aged until three days post mortem on polystyrene plates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
3
3
Order By: Relevance
“…Also on day 3 variations in SL among different breeds were evident. These results contradict those reported by Modika et al [ 37 ] suggesting that meat tenderisation begins immediately after slaughter. The present results suggest that immediately after slaughter, there is a breed related enzymatic proteolytic system activation which can be associated with the muscle nanostructure degradation but not directly linked to tenderness since differences in tenderness related attributes such as SL were evident from day 3.…”
Section: Resultscontrasting
confidence: 99%
“…Also on day 3 variations in SL among different breeds were evident. These results contradict those reported by Modika et al [ 37 ] suggesting that meat tenderisation begins immediately after slaughter. The present results suggest that immediately after slaughter, there is a breed related enzymatic proteolytic system activation which can be associated with the muscle nanostructure degradation but not directly linked to tenderness since differences in tenderness related attributes such as SL were evident from day 3.…”
Section: Resultscontrasting
confidence: 99%
“…In addition, according to the results of the present study, the tenderness of the three cattle types on two different cuts (Senga: sirloin: 5.54 ± 1.90, chunk: 5.25 ± 2.47; Sheko: sirloin: 5.43 ± 2.76, chunk: 6.33 ± 2.28) was in agreement with the findings of [ 47 ], who showed that the muscles of Holstein Friesian bulls were 6.06 ± 0.199, 5.56 ± 0.199, 5.65 ± 0.199 and 5.97 ± 0.199, respectively. Another study reported [ 32 ] that beef muscle tenderness was 26.77 ± 2.202, which was not in line with the present study.…”
Section: Resultscontrasting
confidence: 96%
“…Similarly, Ref. [ 32 ] reported that the mean beef tenderness was 14.26 ± 3.9, which was greater than that in the present study. The difference in tenderness might not be due to the breed effect.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Although consumer visual assessment provides a direct answer to the preferences of consumers, a benefit to using instrumental measurements of color is the possibility of comparing the quantitative values with those found in other studies. Color evaluation is an essential part of meat research (Modika et al., 2015) and important for understanding the quality and the value of beef (Holman et al., 2017). Yet, this task is limited by the lack of establishing objective instrumental thresholds to compare with subjective consumer‐based definitions of acceptable meat color.…”
Section: Effect Of Degree Of Doneness On the Sensory Properties Of Meatmentioning
confidence: 99%